2011
DOI: 10.1212/wnl.0b013e318204a397
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of CSF biomarkers Aβ 1-42 , t-tau, and p-tau 181p in the ADNI cohort

Abstract: Objectives: CSF levels of A␤ 1-42 , t-tau, and p-tau 181p are potential early diagnostic markers for probable Alzheimer disease (AD). The influence of genetic variation on these markers has been investigated for candidate genes but not on a genome-wide basis. We report a genome-wide association study (GWAS) of CSF biomarkers (A␤ 1-42 , t-tau, p-tau 181p , p-tau 181p /A␤ 1-42 , and t-tau/A␤ GLOSSARY A␤ 1-42 ϭ amyloid-␤ 1-42 peptide; AD ϭ Alzheimer disease; ADNI ϭ Alzheimer's Disease Neuroimaging Initiative; G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
155
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 40 publications
11
155
1
2
Order By: Relevance
“…The 523 VL poly T resulted in significantly higher expression than the S poly T. These results suggest that the 523 locus may contribute to LOAD susceptibility by modulating the expression of TOMM40 and/or APOE transcription [55]. Recent studies also suggest that the TOMM40 gene rs10524523 ("523") variable length poly T repeat polymorphism is associated to a certain extent with similar AD phenotypes as those reported for APOE, such as brain white matter changes [56,57] or different biomarkers [58][59][60][61]. In addition, the TOMM40 rs2075650 G allele may be a risk factor for the development of depression [62] and sporadic inclusion body myositis [63].…”
Section: Introductionmentioning
confidence: 76%
“…The 523 VL poly T resulted in significantly higher expression than the S poly T. These results suggest that the 523 locus may contribute to LOAD susceptibility by modulating the expression of TOMM40 and/or APOE transcription [55]. Recent studies also suggest that the TOMM40 gene rs10524523 ("523") variable length poly T repeat polymorphism is associated to a certain extent with similar AD phenotypes as those reported for APOE, such as brain white matter changes [56,57] or different biomarkers [58][59][60][61]. In addition, the TOMM40 rs2075650 G allele may be a risk factor for the development of depression [62] and sporadic inclusion body myositis [63].…”
Section: Introductionmentioning
confidence: 76%
“…Han et al [53] found CYP19A1 and NCAM2 to be associated with AD biomarkers in cerebrospinal fluid (CSF) including b-amyloid peptide (Ab 1-42 ), total tau protein, and phosphorylated tau (P-tau 181P ). Using the same AD biomarkers in CSF as Han et al, Kim et al [54] showed that APOE, LOC100129500, TOMM40, and EPC2 had genome-wide significance. By performing so far the largest GWAS using AD biomarkers in CSF, Cruchaga et al [55] revealed the association of GLIS3 and TREM with AD.…”
Section: Ad Biomarkers From Neuroimaging and In Fluids As The Phenotypementioning
confidence: 99%
“…Genetic variants of the neuronal sortilin-related receptor with A-type repeats (SORL1, also called LR11 or SORL A) have been found to be risk factors for the development of Alzheimer's Disease (AD). Significant relation between CSF Aβ (1-42) levels and the SORL1 SNPs 23 and 24 were identified in the AD group (Kim et al, 2011). In addition to known candidate genes, APOE, TOMM40 and one hypothetical gene LOC100129500 partially overlapping APOE; one novel gene, EPC2 and certain other genes were associated with CSF biomarkers that are related to AD.…”
Section: Ajnmentioning
confidence: 92%